A Capacitive Pressure Sensor with Linearity and High Sensitivity over a Wide Pressure Range using Thermoplastic Microspheres - Yusaku Tagawa; Sunghoon Lee; Takao Someya; Tomoyuki Yokota (Advanced Electronic Materials, 2023)
Abstract A flexible pressure sensor with a linear response over a wide pressure range with high sensitivity is extremely desirable for high‐pressure applications, such as monitoring body weight and plantar pressure distributions. As a promising candidate to achieve the high sensitivity, a porous structure in capacitive pressure sensors is essential. However, this structure invokes the early saturation of sensitivity owing to a low compression modulus. In this study, thermoplastic microspheres (TPM) as porous materials are utilized, and demonstrate a solution‐processed simple structure that is highly sensitive (3.1 × 10−3 kPa−1) over a wide pressure range (1 MPa) with linearity (R2 = 0.996). The TPM‐containing pressure sensor responds within 100 ms and can withstand a 10 000 times cyclic test under 150 kPa. The linearity may be attributed to the rigid characteristics of the TPM‐containing membrane. These results show that the TPM‐containing pressure sensor has sufficient sensitivity and linearity to reduce the need for complex system calibrations and has potential applications in pressure distribution and weight monitoring.